Circular polarimetry of suspect wind-accreting magnetic pre-polars. Issue 3 (25th April 2022) - Hakala, Pasi; Parsons, Steven G; Marsh, Thomas R; Gänsicke, Boris T; Ramsay, Gavin; Schwope, Axel; Hermes, J J
ABSTRACT: We present results from a circular polarimetric survey of candidate detached magnetic white dwarf – M dwarf binaries obtained using the Nordic Optical Telescope, La Palma. We obtained phase resolved spectropolarimetry and imaging polarimetry of seven systems, five of which show clearly variable circular polarisation. The data indicate that these targets have white dwarfs with magnetic field strengths >80 MG. Our study reveals that cyclotron emission can dominate the optical luminosity at wavelengths corresponding to the cyclotron emission harmonics, even in systems where the white dwarfs are only wind-accreting. This implies that a very significant fraction of the stellar wind of the companion star is captured by the magnetic white dwarf reducing the magnetic braking in pre-cataclysmic variables (CVs). Furthermore, the polarimetric confirmation of several detached, wind-accreting magnetic systems provides observational constraints on the models of magnetic CV evolution and white dwarf magnetic field generation. We also find that the white dwarf magnetic field configuration in at least two of these systems appears to be very complex.